CHRONIC EATING DISORDERS IN YOUNG CHILDREN - OBESITY (PARATROPHIA): PATHOGENETIC MECHANISMS, RISK FACTORS, PREVENTION AND NUTRITION CORRECTION (LECTURE) - Наталья Николаевна Миняйлова; Юрий Иванович Ровда; Наталья Степановна Черных (The Publishing House Medicine and Enlightenment, 2021)
The article covers the issues of terminology, classification, etiology and diagnostic of excessive nutrition in young children. It presents the risk factors of overweight and obesity in accordance with the age. It also reflects the aspects of breastfeeding of newborns with macrosomia and young children with overweight.